Swedish-Finnish Social Word List - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Sweden Finnish social word list contains the main vocabulary in social insurance, elder and youth care, family law, health care and nursing, drug abuse and treatment, and refugee admission. Approximately 3700 entries. 2011.

Svensk-sverigefinsk socialordlista innehåller det centrala ordförrådet inom socialförsäkring, äldre- och ungdomsvård, familjerätt, hälso- och sjukvård, missbruks- och beroendebehandling och flyktingmottagning. Ca 3700 uppslagsord. 2011.
Svensk-finsk socialordlista
Keywords: social services; socialtjänst; Psychology, Social; Socialpsykologi; delinquency; brottslighet; antisocial behaviour; asocialt beteende; social work; socialt arbete; social psychology; socialpsykologi; Public Policy; Socialpolitik; Social Security; Socialförsäkring; Social Work; Socialt arbete; glossary; ordlista; social policy; socialpolitik; social service; socialtjänst; social system; socialsystem; social welfare; socialvård; sociology; political science; social science; welfare policy; social- och välfärdspolitik; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur